Pengaruh Baby Massage Dengan Minyak Essensial Mawar Terhadap Kualitas Tidur Bayi Usia 6 – 12 Bulan Di BPM Rahayu - Handayani, Welly; Nisa, Setia (-, 2025)
This study aimed to determine the effect of baby massage using rose essential oil on the sleep quality of infants aged 6–12 months at BPM Rahayu. This research employed a pre-experimental design with a one-group pretest–posttest approach. The sample consisted of 15 infants selected using accidental sampling. Infant sleep quality was measured before and after the intervention using a structured sleep quality questionnaire. Data were analyzed using the Wilcoxon Signed Rank Test. The results showed that before the intervention, all infants (100%) had moderate sleep quality, whereas after the intervention, all infants (100%) experienced good sleep quality. Statistical analysis revealed a significant difference in sleep quality before and after the intervention (p = 0.000 0.05). These findings indicate that baby massage combined with rose essential oil has a significant effect on improving sleep quality in infants aged 6–12 months. Baby massage with rose essential oil can be applied as an effective non-pharmacological intervention to support optimal infant growth and development.